The effect of LED lighting on photosynthetic parameters and weight of lamb’s lettuce (Valerianella locusta) - Wojciechowska Renata; Kołton Anna; Długosz-Grochowska Olga; Żupnik Marek; Grzesiak Wojciech (Folia Horticulturae, 2013)
The experiment was carried out in the winter and autumn of 2011 using lamb’s lettuce (Valerianella locusta Laterr. Em Betce) as a test plant under greenhouse growing conditions. The aim of the study was to evaluate the effect of a prolonged day with modern SSL LED (Solid State Lighting Light Emitting Diodes) technology on photosynthetic parameters and plant yield. Two kinds of LED lamps with different spectral properties were used. The first emitted a white light and the second a mixture of red and blue light. Measurements of chlorophyll fluorescence and gas exchange were taken in natural and artificial light. Control plants were not treated with additional lighting. During the day with natural light in March (winter growing), photosynthesis intensity, stomatal conductance and transpiration of lamb’s lettuce leaves were higher than in November (autumn growing). In the evening hours of March and November, during artificial plant lighting, similar photosynthesis intensity was observed. This intensity was significantly higher than in the afternoon hours (by natural light) in the autumn. The highest content of chlorophyll a, b and carotenoids was found in the treatment with red+blue LEDs in winter growing. Supplemental lighting with red+blue LED light stimulated the high efficiency of the photosynthetic apparatus, which was manifested by the highest Performance Index (PI). The highest weight of the rosettes was noted in the autumn growing period in plants that were under the influence of the red+blue supplemental lighting followed by the white LED. This could be the result of a significant stimulation of photosynthesis during supplemental lighting with the LED lamps during this period.